2007
DOI: 10.1002/jobm.200610203
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial exopolysaccharides – a perception

Abstract: Microbial polysaccharides are multifunctional and can be divided into intracellular polysaccharides, structural polysaccharides and extracellular polysaccharides or exopolysaccharides (EPS). Extracellular polymeric substances (EPS), produced by both prokaryotes (eubacteria and archaebacteria) and eukaryotes (phytoplankton, fungi, and algae), have been of topical research interest. Newer approaches are carried out today to replace the traditionally used plant gums by their bacterial counterparts. The bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(160 citation statements)
references
References 79 publications
2
139
0
3
Order By: Relevance
“…110 For many encapsulated bacteria, polysaccharides are major determinants for survival, promoting host virulence, protection from desiccation, and protection from phagocytosis and antimicrobials. [111][112][113] For phage, polysaccharides can pose as a physical barrier to the cell surface receptors needed for adsorption. Polysaccharides are classified based on their morphological localization as being either intracellular polysaccharides, structural polysaccharides (i.e.…”
Section: Virion-associated Peptidoglycan Hydrolasesmentioning
confidence: 99%
“…110 For many encapsulated bacteria, polysaccharides are major determinants for survival, promoting host virulence, protection from desiccation, and protection from phagocytosis and antimicrobials. [111][112][113] For phage, polysaccharides can pose as a physical barrier to the cell surface receptors needed for adsorption. Polysaccharides are classified based on their morphological localization as being either intracellular polysaccharides, structural polysaccharides (i.e.…”
Section: Virion-associated Peptidoglycan Hydrolasesmentioning
confidence: 99%
“…The type of carbon and nitrogen supplied as nutrients to bacteria are known to influence the EPS yields depending on their composition and relative amounts [19,31,32]. The influence of the carbon substrate on growth and EPS production by G. hansenii LMG1524 was studied in a medium containing a salt base (see Materials and Methods), 10 g/L of the carbon substrate and 1.5 g/L of sodium glutamate as the nitrogen source.…”
Section: Effects Of Carbon and Nitrogen Sources On Bacterial Growth Amentioning
confidence: 99%
“…The EPS production yield of a bacterium is influenced by culture conditions and medium composition [19,20]. Furthermore, the design of these parameters is important for improving the efficiency of synthesis in liquid medium.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the highest EPS production of the strain in the sucrose containing medium. Qiang et al (18) 4 , and NaNO 3 ) were studied to define an optimal medium. A significant increase in the levan yield from 5.27 up to 15.42 g.L -1 under these conditions was found (19).…”
Section: Discussionmentioning
confidence: 99%
“…tion (4). Carbon and nitrogen sources generally play a significant role, because these nutrients are directly linked to the cell proliferation and metabolite biosynthesis (5,6).…”
mentioning
confidence: 99%